On the question of the physical fitness of an employee of the internal affairs bodies for the suppression of offenses in various situations - T. Baksheva; A. Zemlyanoy; D. Petrenko (Вестник Северо-Кавказского федерального университета, 2022)
The article is devoted to the problem of identifying effective ways to train employees of internal affairs bodies to use physical force in difficult situations of official activity. The purpose of the article is the implementation in practice of situational training methods that contribute to the formation of skills in the use of physical force in difficult situations of official activity among employees of internal affairs bodies. The main conclusions and results of the work were scientific judgments on the importance of the development of professionally significant physical qualities, such as endurance, strength, speed and dexterity in the conditions of modeling operational and service situations of a police officer. According to the authors, obstacle courses are the most acceptable and generally available means for pedagogical modeling. The novelty in the work is presented by the authors in the interpretation of the methodology of physical fitness of a police officer, as close as possible to the activity of suppressing the actions of the offender.